1967
DOI: 10.1111/j.1469-8749.1967.tb02212.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep States in Premature Infants

Abstract: SUMMARY Suggestions that rapid eye movement (REM) sleep is ontogenetically primitive and observations of the behaviour of premature infants led to an attempt to trace the development of sleep in human infants from the premature period to three months after the expected date of delivery. Three sleep states were established, Quiet Sleep, Active Sleep (REM sleep), and Transitional Sleep, for the categorization of each 20 second interval of sleep during lengthy electroence‐phalographic and polygraphic recordings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
1
1

Year Published

1968
1968
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(50 citation statements)
references
References 7 publications
(1 reference statement)
0
48
1
1
Order By: Relevance
“…Subsequently, we will discuss the different measurement methods used to acquire signals connected to sleep states in preterm infants, before discussing some unobtrusive technical means for acquiring these signals. (4,5). More information on the role of each of these sleep states during development is available (6)(7)(8).…”
Section: Accepted Manuscriptmentioning
confidence: 92%
See 1 more Smart Citation
“…Subsequently, we will discuss the different measurement methods used to acquire signals connected to sleep states in preterm infants, before discussing some unobtrusive technical means for acquiring these signals. (4,5). More information on the role of each of these sleep states during development is available (6)(7)(8).…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…The scoring parameters of both methods can be found in the corresponding publications (16). There are three ways to perform classification using the two methods: the use of PSG methods alone (1,(17)(18)(19)(20), the use of behavioural methods alone (13,14,21,22) and the use of both methods in combination (4,11,16,(23)(24)(25). However, sleep/wake states in EEG or PSG of preterm infants are typically scored manually.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Earlier infant scoring criteria have tried to reduce the percentages of T sleep scored by permitting scoring if only one, or better yet, two PSG correlates within an epoch are discordant for the sleep state. 24,90 The percentage of sleep time spent in T sleep decreases with increasing infant maturation. Figure 5 shows an example of T sleep.…”
Section: Transitional Sleep (T)mentioning
confidence: 99%
“…Although it may appear futile to question to what extent they reflect wakefulness, as this notion cannot be tested in fetal life, some authors have suggested that certain early fetal movements are reminiscent of postnatal movement patterns seen during wakefulness. 18 Clearly rhythmical cycling of motor activity appears between 20 and 28 weeks of gestation 12,19 (Fig. 1).…”
mentioning
confidence: 97%
“…In particular, concordance between behavioural and EEG variables is poor. 12 Transition between states occurs discontinuously, relatively frequently over short intervals, and can sometimes be provoked by stimulation at some moments but not at others. This may continue up to the age of 6 months.…”
mentioning
confidence: 99%